2001
DOI: 10.2337/diacare.24.5.919
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ACE Activity Is Insufficient to Decrease Microalbuminuria in Normotensive Patients With Type 1 Diabetes

Abstract: OBJECTIVE -To study whether administration of 1.25 and 5.0 mg ramipril daily, compared with placebo treatment, reduces the urinary albumin excretion rate (UAER) in normotensive patients with type 1 diabetes.RESEARCH DESIGN AND METHODS -Ramipril was administered double blind at two different doses (1.25 [n ϭ 19] and 5.0 mg [n ϭ 18]), and compared with placebo (n ϭ 18) after a single-blind placebo period of 1-4 weeks. The patients (total, n ϭ 55; women, n ϭ 14) were followed for 2 years. To document an effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Because population-based data demonstrate a continued increase in the new cases of end-stage renal disease (ESRD) due to diabetes in the United States-even well into the era of frequent ACEI use-there appears to be an inconsistency between the optimistic view of ACEIs from clinical trial data and the real world setting [27,33]. Also, a beneficial effect on albumin excretion has not been unanimously observed in all studies [34].…”
Section: Microalbuminuria Progressionmentioning
confidence: 98%
“…Because population-based data demonstrate a continued increase in the new cases of end-stage renal disease (ESRD) due to diabetes in the United States-even well into the era of frequent ACEI use-there appears to be an inconsistency between the optimistic view of ACEIs from clinical trial data and the real world setting [27,33]. Also, a beneficial effect on albumin excretion has not been unanimously observed in all studies [34].…”
Section: Microalbuminuria Progressionmentioning
confidence: 98%
“…We also measured the basal serum levels of urea nitrogen, sodium, potassium, creatinine, glucose, cholesterol, triglycerides, and peripheral plasma renin activity (PRA) and aldosterone. PRA and aldosterone were measured both in supine and upright position, as previously reported [21]. Ventricular ejection fraction was measured by echocardiography as previously reported by our group [14] and in accord with De Simone et al [22].…”
Section: Protocolmentioning
confidence: 98%
“…The mechanism of no reduction in BP with perindopril in the present study is not understood, although several studies have reported that chronic treatment with ACE inhibitors did not change BP in wellcontrolled hypertensive or normotensive patients with DM. [22][23][24] Even in hypertensive patients, almost 30% of the patients in one study were non-responders (no significant fall in BP) to ACE inhibitors and that the fall in BP by ACE inhibitors was related to pre-treatment plasma renin activity. 25 However, we did not measure plasma renin activity, serum ACE activity or plasma angiotensin II level in this study.…”
Section: Effects Of Ace Inhibition On Adma and Vwfmentioning
confidence: 99%